Charles Lever, His Life in His Letters, Vol. II - Lever, Charles, 1806-1872; Downey, Edmund, 1856-1937 (Salt Lake City, UT : Project Gutenberg, 2011)
"Charles Lever: His Life in His Letters, Vol. II" by Charles James Lever is a collection of personal correspondence that provides insights into the author's life and thoughts, composed in the early 20th century. This volume features letters that reveal Lever's experiences in Florence, his interactions with significant figures of his time, and his reflections on his writing career, particularly in relation to his well-known work, "Tony Butler." The book captures the essence of Lever's literary pursuits while intertwining it with the tumultuous historical backdrop of Italy during the 1860s. The opening of this correspondence highlights Lever's anxieties and ambitions surrounding his writing, specifically his serial story "Tony." It begins with a letter to Mr. John Blackwood, expressing gratitude for his criticism and support, and discussing ideas for the development of the narrative. Lever also touches on personal challenges, such as health struggles, and the social dynamics of his time, illustrating a blend of professional concern and personal reflection. Through these letters, readers are introduced to Lever's literary world, his quest for success, and the relationships that influenced his work against the vivid backdrop of a changing Italy. (This is an automatically generated summary.)
Release date is 2011-04-13
Produced by David Widger
Keywords: Lever, Charles James, 1806-1872 -- Correspondence; Novelists, Irish -- 19th century -- Correspondence